Selective initiation of replication at origin sequences of the rDNA molecule of Physarum polycephalum using synchronous plasmodial extracts. - Daniel, D C (1989)
A cell-free system using synchronous plasmodial extracts initiates replication selectively on the 60 kb rDNA palindrome of Physarum polycephalum. Preferential labeling of rDNA fragments by nuclear extracts, in which elongation is limited, indicates that initiation occurs at two positions corresponding to in vivo origins of replication estimated by electron microscopy. Both nuclear and whole plasmodial extracts initiate selectively within a plasmid, pPHR21, containing one of these origins. In this plasmid bubbles expand bidirectionally and generate DpnI-resistant DNA. Extracts made at prophase or early S phase, times when the nucleolus is disorganized, are most active in pPHR21 replication. Mapping positions of replication bubbles locates the initiation point in a 3.2 kb BstEII fragment at the upstream border of a series of 31 bp repeats 2.4 kb from the initiation point for ribosomal gene transcription.